Regional Expression of Act-MMP3 Contributes to the Selective Loss of Neurons in Ganglion Cell Layers following Acute Retinal ischemia/Reperfusion Injury. (3rd May 2020) - Hu, Tu; Wang, Shuchao; Zeng, Leping; Xiong, Kun; Chen, Dan; Huang, Jufang
ABSTRACT: Purpose : Evidences suggest that during ischemia/reperfusion events, neuronal loss in ganglion cell layers (GCLs) occurs initially in the peripheral retinae followed by the central. However, which key molecule or factor mediates this selective loss needs elucidation. In the present study, we detected the regional expression of active matrix metalloproteinase 3 (Act-MMP3) in the central and peripheral rat retinae following acute retinal ischemia/reperfusion (RI/R) injury and explored the effects and mechanisms of this regional expression on the selective neuronal loss in GCLs. Methods : QPCR and Western Blotting were used to detect the expression of Act-MMP3 in the central part and peripheral part of the adult rat retinae. Immunofluorescence and double immunofluorescence were used to assess the number of NeuN-positive cells in the GCLs and Iba-1+CD 68-positive cells were determined. Additionally, the Linear-regression analysis was performed to test the correlation between the ODV of Act-MMP3 and the neuronal loss in the GCLs/Iba-1+CD 68 positive cells in retinae. Results : An evident up-regulation of active matrix metalloproteinase 3 (Act-MMP3) in peripheral retinae preceded to that in central region following acute RI/R. We found Act-MMP3 up-regulation to be associated with the selective neuronal loss in GCLs (central: r = 0.7566, p < .0001, r 2 = 0.5724; peripheral: r = 0.8241, p < .0001, r 2 = 0.6792). Suppressing Act-MMP3 ameliorated the selective neuronal loss in GCLs following acute RI/R. Furthermore, the activation of microglia in the peripheral retinae also preceded to that in the central and was found to be correlated with the regional expression of Act-MMP3 (Central: r = 0.8540, p < .0001, r 2 = 0.7294; Peripheral: r = 0.7820, p < .0001, r 2 = 0.6116). Suppressing Act-MMP3 ameliorated the microglia regional activation following acute RI/R. Conclusion : The regional expression of Act-MMP3 in the rat retinae may contribute to the selective neuronal loss in GCLs and microglia regional activation in acute RI/R.